Prevalence of dementia in mainland China, Hong Kong and Taiwan: an updated systematic review and meta-analysis. (12th February 2018) - Wu, Yu-Tzu; Ali, Gemma-Claire; Guerchet, Maëlenn; Prina, A Matthew; Chan, Kit Yee; Prince, Martin; Brayne, Carol
Abstract: Background: There are several existing systematic reviews of prevalence of dementia for mainland China, Hong Kong and Taiwan, but several studies have been newly reported. The aim of this study is to update prevalence data in this region and test for variation across geographical areas and time periods using the new dataset. Methods: Twenty prevalence studies identified from World Alzheimer Report 2015 (January 2011–March 2015) and an updated search (March 2015–February 2017) were added to the original dataset ( N = 76). Meta-regression was used to investigate geographical variation and time trends, taking methodological factors and characteristics of study population into account, and to estimate prevalence and number of people with dementia by geographical area. Results: Compared with northern China, the prevalence of dementia was lower in the central China [-1.0; 95% confidence interval (CI):−2.2, 0.3], south China (−1.7; 95% CI: −3.1, −0.3), Hong Kong and Taiwan (−3.0; 95% CI: −5.0, −1.0) but appeared to be higher in western China (2.8; 95% CI: 0.1, 5.5) after adjusting for methodological variation. The increasing trend from pre-1990 to post-2010 periods was considerably attenuated when taking into account methodological factors and geographical areas. The updated estimated number of people with dementia in all these areas is 9.5 million (5.3%; 95% CI: 4.3, 6.3) in the population aged 60 or above. Conclusions: Geographical variation in dementia prevalence is confirmed in this update, whereas evidence on increasing trends is still insufficient. Differing societal development across areas provides an opportunity to investigate risk factors at the population level operating across diverse life course experiences. Such research could advance global primary prevention of dementia.